1985
DOI: 10.1037/0278-7393.11.3.579
|View full text |Cite
|
Sign up to set email alerts
|

Some effects of color on naming and recognition of objects.

Abstract: In this article, we investigated the role of color in the recognition and naming of everyday objects. In the first experiment we found that color pictures were named faster than black-and-white and that shape information did not facilitate color naming. Experiment 2 was carried out to determine at which stage of object processing the color facilitation occurred. We found that color had no effect on object recognition but did facilitate object naming, even when color was redundant for discrimination. This did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
95
1
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 30 publications
9
95
1
1
Order By: Relevance
“…Studies of recognition at the basic level (Rosch, Mervis, Johnson, Grey, & BoyesBraem, 1976) revealed that subjects verified pictures of common objects equally fast whether they were colored or not (Biederman & Ju, 1988;Davidoff & Ostergaard, 1988;Ostergaard & Davidoff, 1985). Consistent with the idea that colors play no role in bootstrapping recognition, Ostergaard and Davidoff (1985) found that objects were verified equally fast, irrespective of whether they were properly colored. Colors, however, should at least inform the recognition of some objects.…”
Section: Luminance Color and Recognitionmentioning
confidence: 96%
See 2 more Smart Citations
“…Studies of recognition at the basic level (Rosch, Mervis, Johnson, Grey, & BoyesBraem, 1976) revealed that subjects verified pictures of common objects equally fast whether they were colored or not (Biederman & Ju, 1988;Davidoff & Ostergaard, 1988;Ostergaard & Davidoff, 1985). Consistent with the idea that colors play no role in bootstrapping recognition, Ostergaard and Davidoff (1985) found that objects were verified equally fast, irrespective of whether they were properly colored. Colors, however, should at least inform the recognition of some objects.…”
Section: Luminance Color and Recognitionmentioning
confidence: 96%
“…When the activated representation comprises color cues, if these participate in recognition, then matching should be better with colored than with achromatic versions of the same object (Biederman & Ju, 1988;Joseph & Proffitt, 1996;Sanocki, Bowyer, Heath, & Sarkar, 1998). Studies of recognition at the basic level (Rosch, Mervis, Johnson, Grey, & BoyesBraem, 1976) revealed that subjects verified pictures of common objects equally fast whether they were colored or not (Biederman & Ju, 1988;Davidoff & Ostergaard, 1988;Ostergaard & Davidoff, 1985). Consistent with the idea that colors play no role in bootstrapping recognition, Ostergaard and Davidoff (1985) found that objects were verified equally fast, irrespective of whether they were properly colored.…”
Section: Luminance Color and Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research into object recognition has typically found that surface colour facilitates object naming but does not facilitate performance in object classification or object verification tasks. For instance, Ostergaard and Davidoff (1985) found that presenting participants with colour photographs instead of black-and-white photographs facilitated object naming. Similarly, Williams and Tanaka (2000; as cited in Naor- Raz et al, 2003) observed that participants were faster to name an object with a typical colour such as a banana when presented with colour pictures than when presented with line drawings.…”
Section: The Influence Of Colour On Object Recognition and Classificamentioning
confidence: 99%
“…Chromatic variations provide the visual system with the means to gain invariance and specificity, colour having been shown to provide benefit in visual segmentation, recognition, identification and classification (Davidoff and Oostergaard 1988;Gegenfurtner and Rieger 2000;Gegenfurtner et al 1998;Kingdom 2003; L/M-Opponency 4 Oostergaard and Davidoff 1985). Conversely, studies have shown that luminance cues support the recognition of faces, objects and scenes Parker et al 1998;Parker et al 1992;Schyns and Oliva 1994, 1997Sergent 1986).…”
mentioning
confidence: 99%